2011
DOI: 10.1155/2011/264173
|View full text |Cite
|
Sign up to set email alerts
|

Schistosome: Its Benefit and Harm in Patients Suffering from Concomitant Diseases

Abstract: Schistosomiasis is an important tropical disease affecting approximately 200 million people worldwide. Because of its chronicity and robust immunomodulatory activity, the effects of schistosomes on other diseases, such as allergies, autoimmunity, and infectious diseases, have been studied extensively in both epidemiological and experimental settings. In this paper, we summarize the beneficial and harmful effects of schistosomes. The importance of controlling schistosomiasis is also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 104 publications
3
18
1
Order By: Relevance
“…Within our study, we found that HCV patients with schistosoma co‐infection had significantly higher liver transaminases levels as well as elevated HCV‐RNA titres, indicating that concomitant schistosome infection indeed aggravates liver disease and inhibits virus elimination. As previous studies revealed that ALT and AST levels in endemic normals and S. mansoni ‐mono‐infected individuals were comparable (El‐Kady et al ., 2005), our current findings substantiate other studies performed in Egypt demonstrating aggravated liver disease and less controlled viral replication in schistosome‐co‐infected HCV patients . Viral clearance is known to correlate with strong and sustained virus‐specific CD4 + and CD8 + T‐cell responses during acute HBV infection , and chronicity develops in such individuals who fail to mount or sustain such responses .…”
Section: Discussionsupporting
confidence: 89%
“…Within our study, we found that HCV patients with schistosoma co‐infection had significantly higher liver transaminases levels as well as elevated HCV‐RNA titres, indicating that concomitant schistosome infection indeed aggravates liver disease and inhibits virus elimination. As previous studies revealed that ALT and AST levels in endemic normals and S. mansoni ‐mono‐infected individuals were comparable (El‐Kady et al ., 2005), our current findings substantiate other studies performed in Egypt demonstrating aggravated liver disease and less controlled viral replication in schistosome‐co‐infected HCV patients . Viral clearance is known to correlate with strong and sustained virus‐specific CD4 + and CD8 + T‐cell responses during acute HBV infection , and chronicity develops in such individuals who fail to mount or sustain such responses .…”
Section: Discussionsupporting
confidence: 89%
“…These suggest that helminth co-infection might thus impair the mechanisms necessary to control leishmaniasis. The current immunomodulatory explanation is in concurrence with observations in murine models, where co-infection of L. major and S. mansoni exacerbated lesion development compared to mice infected with L. major alone [22-24,35]. The action of helminth infection affecting the immune response of the host, may increase protozoan multiplication substantially thus enhancing leishmaniasis severity [23,24,26].…”
Section: Introductionsupporting
confidence: 78%
“…The current study is designed to determine if this situation influences standard adult immunizations in those who have or do not have S . mansoni infections at the time of their immunizations [7]. …”
Section: Introductionmentioning
confidence: 99%